2004
DOI: 10.1038/oby.2004.268
|View full text |Cite
|
Sign up to set email alerts
|

Covariability in Diet and Physical Activity in African‐American Girls

Abstract: Covariability in diet and physical activity in African-American girls. Obes Res. 2004;12:46S-54S. Objective: Our goal was to examine 12-week covariability in diet and physical activity changes among 8-to 10-yearold African-American girls and if these changes predicted percent change in BMI. Research Methods and Procedures: Covariability among percent changes [(post Ϫ pre)/pre ϫ 100] in nutrients, food groups, and physical activity was assessed among 127 8-to 10-year-old African-American girls. Pearson correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
7
1
Order By: Relevance
“…Additionally, the control group received a PA intervention (Jago et al, 2006) which could have increased their desire to make healthier dietary choices. However, there was no covariability of changed diet and PA behaviors in this or an earlier study (Thompson et al, 2004). It is possible that outliers could have influenced LV consumption results.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Additionally, the control group received a PA intervention (Jago et al, 2006) which could have increased their desire to make healthier dietary choices. However, there was no covariability of changed diet and PA behaviors in this or an earlier study (Thompson et al, 2004). It is possible that outliers could have influenced LV consumption results.…”
Section: Discussionmentioning
confidence: 76%
“…Changes at post-1 and post-2 relative to baseline (Thompson et al, 2004) were calculated. Pearson correlations determined if changes in FJ and LV consumption covaried with changes in PA.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few studies assessing the association between dietary behaviours and PA using objective PA data ( 11 , 29 ) , but, to our knowledge, this is the first study examining the association between breakfast frequency and objectively measuring PA in adolescents. Two previous studies using objective monitoring to assess PA and diet have shown conflicting results, with one showing that PA and fat consumption were inversely related ( 29 ) and the other indicating no relationship between change in diet or PA ( 11 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criteria in this study are routinely used in similar studies (31, 32); however, approximately 2% of children had WHZ >3.5 SD and were, therefore, excluded from the analysis. While measurements outside this range are typically errors, it is possible that children who were grossly overweight were excluded unnecessarily.…”
Section: Discussionmentioning
confidence: 99%